Epidemiology of Genu Varum Patients In Dr. Soetomo General Academic Hospital Surabaya 2010-2018: A Retrospective Study - Hidayatullah, Ronaa Nuqtho; Martanto, Tri Wahyu (Universitas Airlangga, 2022)
Background: Genu varum is a condition where the legs bend inward, resembling the letter